Review of thermoelectric generation for internal combustion engine waste heat recovery. (July 2022) - Burnete, Nicolae Vlad; Mariasiu, Florin; Depcik, Christopher; Barabas, Istvan; Moldovanu, Dan
Abstract: With the current emphasis on electrified vehicles, the use of internal combustion engines (ICEs) as the main propulsion source is challenged, especially for passenger cars. Even though this is not yet the case for freight transportation and the internal combustion engine is still considered the short to mid-term solution, significant improvements in its efficiency and pollutant emissions are required. An energy distribution analysis shows that the internal combustion engine already has two important heat rejection sources representing approximately 65–70% of the energy input: the exhaust gas system (∼35–40%) and the radiator (∼30%). Partially recovering some of this otherwise wasted heat can improve overall thermal efficiency. Compared to other thermal energy recovery methods (Organic Rankine Cycle, mechanical or electrical turbocompounding, etc.), thermoelectric generators have numerous advantages: environmentally friendly, no moving parts, little to no noise and vibration, no working fluids, high reliability (when working temperatures are not exceeded), low maintenance, scalable, modular, ability to operate over a wide range of transient temperature conditions, and the direct conversion of thermal energy into electrical energy. This effort seeks to bring together all aspects concerning the use of thermoelectric generators for internal combustion engine waste heat recovery in a comprehensive overview on the issue while aiding researchers and engineers in the development of efficient systems. This is accomplished by delivering two thorough summaries of both experimental and simulation results including, but not limited to the power output and parasitic losses, as well as the gain in efficiency and reduction in fuel consumption. Furthermore, this effort includes a recap of hot side heat exchanger design (e.g., external shape, internal structure, material, test temperature and gas flow velocity, etc.). As a result, the use of thermoelectric generators installed on the exhaust system and in other regions that can provide heat for power generation (i.e., radiator and exhaust gas recirculation) are fully described.